Electromyographic analysis of relevant muscle groups during completion of computer tasks using different computer mouse positions. Issue 2 (3rd April 2017) - Sako, Shunji; Sugiura, Hiromichi; Tanoue, Hironori; Kojima, Makoto; Kono, Mitsunobu; Inaba, Ryoichi
Abstract : Background . We analyzed muscular activity for different computer mouse positions during the completion of a timed computer task and determined whether the different mouse positions could affect muscular activity, productivity and perceived fatigue. Methods . The subjects were nine healthy young men. Two mouse positions were studied: the distal position (DP), with the forearm rested on the desk; the proximal position (PP), with only the wrist rested on the desk. The subjects performed a 16-min task in each position. Surface electromyography data were recorded for the upper back and shoulder muscles. Work productivity and muscular activity were measured for each mouse position. A visual analog scale was used to assess subjective fatigue. Results . Muscular activity was higher in muscle (m.) deltoideus (posterior) for the DP, while it was significantly higher in m. inferior infraspinatus for the PP. The visual analog scale score was significantly higher and work productivity was lower in the PP. Conclusions . We found that using a mouse in the DP rather than the PP leads to less activity of the external rotators, less perceived fatigue and more productivity. This suggests that the DP is preferable to the PP for computer work involving a mouse.